2019
DOI: 10.1021/acs.analchem.9b00477
|View full text |Cite|
|
Sign up to set email alerts
|

Accelerating the Throughput of Affinity Mass Spectrometry-Based Ligand Screening toward a G Protein-Coupled Receptor

Abstract: Affinity mass spectrometry (MS) enables rapid screening of compound mixtures for ligands bound to a specific protein target, yet its current throughput is limited to individually assay pools of 400−2000 compounds. Typical affinity MS screens implemented in pharmaceutical industry laboratories identify putative ligands based on qualitative analysis of compound binding to the target whereas no quantitative information is acquired to discriminate high-and low-affinity ligands in the screening phase. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 35 publications
0
37
0
Order By: Relevance
“…By comparing the selection of 16 benchmark A 2A R ligands from screening compound pools of 480-mix, 2400-mix, 4800-mix, and 20K-mix, they demonstrated that this accelerated affinity MS screening approach, using either the purified receptor or receptor-expressing cell membranes, allowed detection of most high-affinity A 2A R ligands ( K d or K i <5 µM), and significant reduction of protein consumption and MS instrument time. 275 Three new antagonists for A 2A R were identified as a result. It is likely that the throughput of this method could be further increased to assay close to or above 1 million compounds in one pool.…”
Section: Novel Screening Technologymentioning
confidence: 99%
See 3 more Smart Citations
“…By comparing the selection of 16 benchmark A 2A R ligands from screening compound pools of 480-mix, 2400-mix, 4800-mix, and 20K-mix, they demonstrated that this accelerated affinity MS screening approach, using either the purified receptor or receptor-expressing cell membranes, allowed detection of most high-affinity A 2A R ligands ( K d or K i <5 µM), and significant reduction of protein consumption and MS instrument time. 275 Three new antagonists for A 2A R were identified as a result. It is likely that the throughput of this method could be further increased to assay close to or above 1 million compounds in one pool.…”
Section: Novel Screening Technologymentioning
confidence: 99%
“…It is likely that the throughput of this method could be further increased to assay close to or above 1 million compounds in one pool. 275 …”
Section: Novel Screening Technologymentioning
confidence: 99%
See 2 more Smart Citations
“…This work connects MNP with GPCRs in the cell membrane for the first time and highlights its unique function in exploiting bioactive compounds. Lu et al (2019) immobilized the purified receptor, A 2A R or HCAR 2 on nickel agarose beads and coupled them with Q Exactive HF LC‐MS, which enables screening of 20,000 compounds in one pool. Nine new chemical modulators for A 2A R have been discovered.…”
Section: Ba‐ms Relying On Solid‐phase Micro‐extractionmentioning
confidence: 99%